Investigating the Benefits of A Performance Management and Development System at Africa Glass Industries - Ozoekwem, Victor Chinedu (My University, 2014)
The survival of any organization depends on its ability to compete on a high overall performance scale within the industry in which it operates. With an increasing pressure on employees to produce quality products and services that satisfy their clients, it is admitted by scholars that an effective performance management and development system must be adopted and implemented to improve overall organizational performance. The intention of the study is to establish the fact that an effective performance management and development system is a vital tool for the survival and success of an organization. The purpose of the research therefore was to investigate the benefits of an effective performance management and development system at Africa Glass Industry (AGI). The researcher assessed the current performance processes practiced within AGI, and then investigated the benefits of a structured effective and appropriate performance management and development system. This was achieved by analyzing what is functional for the company as well as benchmarking against selected performance processes that exist within the same industry The research was exploratory and qualitative in nature. The data was collected by means of face-to-face interview with employees of AGI Sheerline Johannesburg Reef Branch. The results of the analysis presented a general consensus in support of the benefits of an effective performance management and development system in the organization. There were also issues which demonstrated the absence or lack of an effective performance management and development system at AGI. The priority of the issues, according to employees, was different from ii management’s views. These different approaches to the issues of performance management and development systems depended on their different levels of conceptualization of the performance management both as a concept and practice within AGI. The findings of this study highlighted the significance of the benefits of a performance management and development system as well as providing insight into the perceptions and components of performance management systems. The research also suggested that a performance management system model that focuses on linking organizational performance to the overall organisational vision and strategy was ideal for AGI. In this regard, the researcher recommended the Balanced Scorecard as an appropriate effective performance management and development system for the company. Other issues that were analysed included factors that must be considered for the implementation of an effective performance management system as well as factors that may hinder the process.
MM (P&DM) thesis
Keywords: Performance management systems